ATROF MUHITNI MUHOFAZALASHNING DOLZARBLIGI - Berdimbetova, A. (SCIENCE and SOCIETY, 2016)
The article is devoted to the issues of environmental protection and rational use of natural resources. The author of the article gives recommendations on the elimination of damage and development of ecological education and knowledge.
Keywords: environment protection; living nature; atmosphere; plant; water; ground; animals; rational use